The effect of oral contraceptive use on salivary testosterone concentrations and athlete performance during international field hockey matches - Liam Kilduff (Journal of Science and Medicine in Sport, 2018)
Objectives: To investigate the effect of oral contraceptive (OC) use on salivary testosterone (sal-T) concentrations and performance-related statistics in international field hockey matches.Design: A cohort observational study with repeated measures.Methods: Twenty-three elite female athletes were monitored across four international field hockey matches over a nine-day period. Salivary T was assessed 45min before each match and several match performance statistics were collated; load (i.e. ratings of perceived exertion×playing time), video-derived positive actions (PA) and negative actions (NA), plus coach and player ratings of performance. The sal-T and match performance profiles of OC (n=7) and Non-OC (n=16) players were compared and predictive relationships tested.Results: Pre-match sal-T concentrations were 35% higher in the Non-OC than the OC group (p=0.001), representing a large effect size (ES) difference of 0.96. The OC and Non-OC groups did not differ on any performance statistic (p≥0.348) with ES differences from -0.22 to 0.11. Salivary T was positively related to the number of PA during match play (p=0.017). Additional linkage between sal-T and NA emerged, but with opposing slopes (p=0.008) in the OC (B=-1.783, p=0.030) and Non-OC (B=0.692, p=0.127) groups.Conclusions: OC usage by elite women athletes was accompanied by lower sal-T concentrations, but the performance outputs of the OC and Non-OC groups were similar. This suggests that the T differences had no impact on match performance. On an individual (population-averaged) level, sal-T was associated with PA and NA during these matches, though the response curves predicting NA differed for OC and Non-OC athletes.